Pengaruh Sudut Elektroda Terhadap Sifat Mekanik dan Fisis Baja Karbon Rendah Hasil Proses Pengelasan SMAW - Darmawan, Darmawan; Endriatno, Nanang; Aksar, Prinob (Teknik Mesin Universitas Halu Oleo, 2022)
Analysis of the effect of welding position and electrode movement pattern on hardness,it can be concluded that the electrode movement pattern has an influence on the hardness result. The purpose of this study was to determine the effect of the electrode angle on the mechanical and physical properties of low carbon steel from the SMAW welding process. The research method used is hardness testing and microstructure analysis. The results obtained are that specimens with different electrode angles, namely 300, 450, and 600 produce an average in each welding area such as the weld area, haz area, and different areas where the greater the angle the higher Also the average for each weld area and also on the analysis of microstructure shows that the weld metal area with electrode angles of 300, 450, and 600 shows the same microstructure or does not show any effect. the larger the area of the weld metal with electrode anglesof 300, 450, and 600, the larger the ferrite area, the larger the area of the weld metal with angles of 300, 450, and 600 pearlite grains.Keywords: electrode angle, low carbon steel, microstructure, welding